(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
The article presents data on the biology and morphology of Echinacea purpurea in the conditions of the Mirzachul oasis. The results of the research show the optimal growth and development of the species, which confirms the full-fledged procurement of raw materials in the territories of the Syrdarya region.